Human skin dendritic cell fate is differentially regulated by the monocyte identity factor Kruppel-like factor 4 during steady state and inflammation - Jurkin, Jennifer; Krump, Corinna; Koeffel, Rene; Fieber, Christina; Schuster, Christopher; Brunner, Patrick M.; Borek, Izabela; Eisenwort, Gregor; Lim, Clarice; Mages, Joerg; Lang, Roland; Bauer, Wolfgang; et al. (Journal of Allergy and Clinical Immunology, 2017)
Langerhans cell (LC) networks play key roles in immunity and tolerance at body surfaces. LCs are established prenatally and can be replenished from blood monocytes. Unlike skin-resident dermal DCs (dDCs)/interstitial-type DCs and inflammatory dendritic epidermal cells appearing in dermatitis/eczema lesions, LCs lack key monocyte-affiliated markers. Inversely, LCs express various epithelial genes critical for their long-term peripheral tissue residency.Dendritic cells (DCs) are functionally involved in inflammatory diseases; however, the mechanisms remained poorly understood.In vitro differentiation models of human DCs, gene profiling, gene transduction, and immunohistology were used to identify molecules involved in DC subset specification.Here we identified the monocyte/macrophage lineage identity transcription factor Kruppel-like factor 4 (KLF4) to be inhibited during LC differentiation from human blood monocytes. Conversely, KLF4 is maintained or induced during dermal DC and monocyte-derived dendritic cell/inflammatory dendritic epidermal cell differentiation. We showed that in monocytic cells KLF4 has to be repressed to allow their differentiation into LCs. Moreover, respective KLF4 levels in DC subsets positively correlate with proinflammatory characteristics. We identified epithelial Notch signaling to repress KLF4 in monocytes undergoing LC commitment. Loss of KLF4 in monocytes transcriptionally derepresses Runt-related transcription factor 3 in response to TGF-?1, thereby allowing LC differentiation marked by a low cytokine expression profile.Monocyte differentiation into LCs depends on activation of Notch signaling and the concomitant loss of KLF4.
EVALuna2:7718